2020
DOI: 10.1021/acs.orglett.0c01834
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluoroisopropanol-Promoted Disulfidation and Diselenation of Alkyne, Alkene, and Allene

Abstract: Hexafluoroisopropanol (HFIP)-promoted disulfidation and diselenation of C−C unsaturated bonds is reported. Reactions of unactivated alkyne, alkene, and allene, respectively, with disulfides or diselenides in HFIP led to desired products in good to excellent yields (up to 96%). In contrast, other solvents, such as isopropanol and dichloroethane, could not promote the same reaction. This method revealed an example of HFIP-promoted transformations under the mild conditions, which greatly highlighted the unique re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 83 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…HFIP promotes the diselenation and disulfidation of unsaturated C–C bonds (Scheme ). Conducting the reaction in HFIP with 5 mol % of the catalyst gave full conversion and 93% yield; control reactions revealed that similar yields were attained without the metal catalyst. This activity was reserved for HFIP as other solvents (TFE, i -PrOH, DMSO, DMF, MeCN, DCE, acetone, PhCl, MeNO 2 ) resulted in <5% yield of the desired product.…”
Section: Oxidations and Reductionsmentioning
confidence: 99%
“…HFIP promotes the diselenation and disulfidation of unsaturated C–C bonds (Scheme ). Conducting the reaction in HFIP with 5 mol % of the catalyst gave full conversion and 93% yield; control reactions revealed that similar yields were attained without the metal catalyst. This activity was reserved for HFIP as other solvents (TFE, i -PrOH, DMSO, DMF, MeCN, DCE, acetone, PhCl, MeNO 2 ) resulted in <5% yield of the desired product.…”
Section: Oxidations and Reductionsmentioning
confidence: 99%
“…Mixture of E / Z isomers (>30:1): 1 H NMR (400 MHz, CDCl 3 ) δ 7.58 (d, J = 7.1 Hz, 2H), 7.34–7.31­(m, 3H), 7.30–7.27 (m, 4H), 7.24–7.20 (m, 3H), 7.18 (d, J = 7.7 Hz, 2H), 7.10 (tt, J = 7.4, 1.2 Hz, 1H), 6.87 (s, 1H); 13 C­{ 1 H} NMR (101 MHz, CDCl 3 ) δ 137.3, 135.8, 135.3, 132.5, 130.2­(2C), 129.64­(2C), 129.57, 129.3­(2C), 129.2­(2C), 129.0­(2C), 128.4, 128.3­(2C), 127.2, 126.9; HRMS (ESI-TOF) calcd for C 20 H 17 S 2 [M + H] + m / z 321.0772; found 321.0757. These data are consistent with literature values …”
Section: Methodsmentioning
confidence: 99%
“…The addition reaction is an elegant, atom-efficient way of producing a variety of sulfides, which are in great demand in material, polymer, and chemical science [ 4 , 5 , 6 , 7 , 8 , 9 ]. Investigation of the procedure for the direct involvement of the components of crude oil in chemical syntheses requires an efficient methodology of component assignment.…”
Section: Introductionmentioning
confidence: 99%